2020
DOI: 10.1186/s12893-020-00865-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of platelet rich plasma on the healing of operated sacrococcygeal pilonidal sinus by lay-open technique: a randomized clinical trial

Abstract: Background Sacrococcygeal pilonidal sinus disease (PSD) is an infection of the skin and subcutaneous tissue at the upper part of the natal cleft of the buttocks. Excision and healing by granulation “lay-open” method is still more preferable than other methods of midline closure or using flaps but the healing time is lengthy. The present study was performed to assess the healing promotion effect of platelet-rich plasma (PRP) on the pilonidal sinus wounds treated by the lay-open method. Methods One hundred pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 13 publications
0
30
0
2
Order By: Relevance
“…Restrictions were placed with respect to the language (English), however, no restrictions were placed with respect to the date of publication. At the end of this literature search process, four RCTs [16][17][18][19] fulfilled the PICOS criteria and were selected for review in this study. This process was carried out using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and is summarised in Figure 1.…”
Section: Search Methods For Identification Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Restrictions were placed with respect to the language (English), however, no restrictions were placed with respect to the date of publication. At the end of this literature search process, four RCTs [16][17][18][19] fulfilled the PICOS criteria and were selected for review in this study. This process was carried out using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and is summarised in Figure 1.…”
Section: Search Methods For Identification Of Studiesmentioning
confidence: 99%
“…All of the included studies [16][17][18][19] reported a statistically significant reduction in time to return to work or activities of daily living in the PRP group compared to the control group (MD 9.68 days, 95% CI 9.16-10.21 days, p < 0.00001). The mean time to return to work or normal activities in the PRP group was 18.8 days compared to 30.9 days in the control group (Figure 5).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 3 more Smart Citations